Efficacy of NRET scoring method in paper-and-pen multiple choice test - Pahayahay, Ma. Rosanna Cisneros (Animo Repository, 2017)
Different scoring methods have been introduced through time whose objective is to address partial knowledge in Multiple Choice (MC) test. One of these is the Number Right Elimination Testing (NRET). This study tried to investigate the effectiveness of NRET scoring method in a pen-and-paper MC test in evaluating the level of knowledge of students and in minimizing guessing. Results showed that NRET scores were not similar to Number Right (NR) scores while NRET and Elimination Testing (ET) scores were equivalent to each other. It also showed that not all correct answers in NR scoring method were based on Full Knowledge, while not all incorrect answers were based on Lack of Knowledge or Full Misconception. Furthermore, NRET scoring method also reduced guessing in the low-ability group. Hence, NRET scoring method is an effective tool for evaluating a more comprehensive level of knowledge of students in paper-and-pen MC test. © 2017 American Scientific Publishers All rights reserved.